Subscapularis Repair After Shoulder Arthroplasty. Issue 1 (March 2015) - Cagle, Paul J.; Shukla, Dave R.; Parsons, Bradford O.; Flatow, Evan L.
Abstract : Both anatomic and reverse total shoulder arthroplasty have demonstrated excellent results in patients with arthritis. The deltopectoral approach is commonly utilized for both procedures, and the subscapularis is typically taken down. Multiple variations of subscapularis repairs are known, but subscapularis failure postoperatively can lead to poor clinical outcomes. We present a case of a standard anatomic total shoulder arthroplasty subscapularis repair with a specific suture configuration and a metallic button. In this technique, both Krackow and Mason-Allen suture techniques are utilized to approximate the tendon down to the bone. The patient described recovered quickly after the surgery, and he has demonstrated excellent results. These results are similar to those seen by the senior author while utilizing this technique, and after transitioning to this technique, postoperative subscapularis failures have been infrequently appreciated.